2020
DOI: 10.3390/polym12061300
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Mechanical Properties of the Biocomposites of Miscanthus Biocarbon and Poly(3-Hydroxybutyrate-co-3-Hydroxyvalerate) (PHBV)

Abstract: Miscanthus biocarbon (MB), a renewable resource-based, carbon-rich material, was melt-processed with poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) to produce sustainable biocomposites. The addition of the biocarbon improved the Young’s modulus of PHBV from 3.6 to 5.2 GPa at 30 wt % filler loading. An increase in flexural modulus, up to 48%, was also observed. On the other hand, the strength, elongation-at-break and impact strength decreased. Morphological study of the impact-fractured surfaces showed we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 56 publications
(69 reference statements)
5
23
0
Order By: Relevance
“…A homogeneous dispersion of filler has been found to improve the mechanical and thermal stability of the host biopolymer. The biocomposite with a poor dispersion of filler indicated a rough fractured surface with the appearance of voids, suggesting the poor wetting of filler by the biopolymer matrix [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…A homogeneous dispersion of filler has been found to improve the mechanical and thermal stability of the host biopolymer. The biocomposite with a poor dispersion of filler indicated a rough fractured surface with the appearance of voids, suggesting the poor wetting of filler by the biopolymer matrix [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Miscanthus BC at 650 °C was chosen since lignocellulosic biomass derived BC offers a higher modulus than other sources of BC due to a high stiffness of samples. The increased stiffness is further associated with increased polymer performance [ 21 ]. Since the BC was pyrolyzed at a lower temperature, the BC was able to maintain more surface functionalities than samples pyrolyzed at higher temperatures [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the polymer industry, one of the methods to improve the sustainability of composite production is to valorize biomass waste as natural fillers. Wastes from agricultural residues [ 20 , 21 ], forestry residues [ 22 ], or food industries [ 17 , 23 ] can be diverted from landfills and instead pyrolyzed to become a carbonaceous natural filler. Pyrolysis is the thermochemical conversion of organic matter to biocarbon (BC), bio-oil, and syngas [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The research reported in this paper evolved from our prior work in developing bioplastic-biochar composite packaging that offers improved end-of-life management options while enabling valorization of food waste that would otherwise be landfilled. This work builds upon a rapidly expanding collection of studies published since 2015, summarized in Table 1, that have documented the potential advantages of using biochar as an additive in plastic products due to its favorable characteristics, including high surface area and long-term chemical and physical stability [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Reported improvements in the performance of polymer-biochar composites include enhanced water adsorption, thermal resistance, and stiffness.…”
Section: Introductionmentioning
confidence: 99%